Volunteerism and Life Satisfaction among Older Adults - Bond, Jr., John B. (Canadian Journal of Counselling and Psychotherapy, 2012)
Quality of life, measured by scores on the Life Satisfaction Indcx-A, of 373 preretirees and retirees between the ages of 55 and 74 was analyzed to determine the independent contributions to life satisfaction of age, sex, retirement status, years of education, marital status and volunteer status. Persons donating their time and services through volunteer activities were found to be more satisfied with their lives than their nonvolunteering counterparts. Educational level was also positively related to life satisfaction. No other independent effects were observed. It was suggested that counsellors investigate potential therapeutic effects of volunteer activities.